GLP-1 Receptor Agonists and Coronary Arteries: From Mechanisms to Events - Pahud de Mortanges, Aurélie; Sinaci, Eldem; Salvador, Dante; Bally, Lia; Muka, Taulant; Wilhelm, Matthias; Bano, Arjola (Frontiers in Pharmacology, 2022)
Objective: Glucagon-like peptide-1 receptor agonists (GLP1-RAs) lower plasma glucose through effects on insulin and glucagon secretion and by decelerating gastric emptying. GLP1-RAs have many beneficial effects beyond glycemic control, including a protective role on the cardiovascular system. However, underlying mechanisms linking GLP1-RA with coronary artery disease are complex and not fully elucidated. In this mini-review, we discuss these mechanisms and subsequent clinical events. Data Sources: We searched PubMed and Google Scholar for evidence on GLP1-RAs and coronary events. We did not apply restrictions on article type. We reviewed publications for clinical relevance. Synopsis of Content: In the first part, we review the current evidence concerning the role of GLP1-RAs on potential mechanisms underlying the development of coronary events. Specifically, we discuss the role of GLP1-RAs on atherosclerosis and vasospasms of epicardial coronary arteries, as well as structural/functional changes of coronary microvasculature. In the second part, we summarize the clinical evidence on the impact of GLP1-RAs in the prevention of acute and chronic coronary syndromes and coronary revascularization. We conclude by discussing existing gaps in the literature and proposing directions for future research.